Predicting obesity: a comparative analysis of machine learning models incorporating different features - Rahman, Md.Sakibur; Ahmed, Kaosar; Nafis, Tanvir Alam; Hossain, Md. Ridwan; Majumder, Swapnil (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.